2013
DOI: 10.1590/1414-431x20133103
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of the ELOVL6 gene polymorphism associated with type 2 diabetes mellitus

Abstract: Recent animal studies have indicated that overexpression of the elongation of long-chain fatty acids family member 6 (Elovl6) gene can cause insulin resistance and β-cell dysfunction. These are the major factors involved in the development of type 2 diabetes mellitus (T2DM). To identify the relationship between single nucleotide polymorphisms (SNP) of ELOVL6 and T2DM pathogenesis, we conducted a case-control study of 610 Han Chinese individuals (328 newly diagnosed T2DM and 282 healthy subjects). Insulin resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
0
11
1
Order By: Relevance
“…Elongase of very long chain fatty acids 6 especially catalyzes elongation of n‐SFA and MUFA with 12, 14, and 16 carbons thereby regulating de novo lipogenesis . ELOVL6 gene polymorphisms were associated with risk of insulin resistance and type 2 diabetes mellitus in European and Han Chinese populations . Moreover, both ELOVL6 and its upstream epidermal growth factor gene are significantly associated with gout in a Han Chinese population .…”
Section: Discussionmentioning
confidence: 99%
“…Elongase of very long chain fatty acids 6 especially catalyzes elongation of n‐SFA and MUFA with 12, 14, and 16 carbons thereby regulating de novo lipogenesis . ELOVL6 gene polymorphisms were associated with risk of insulin resistance and type 2 diabetes mellitus in European and Han Chinese populations . Moreover, both ELOVL6 and its upstream epidermal growth factor gene are significantly associated with gout in a Han Chinese population .…”
Section: Discussionmentioning
confidence: 99%
“…Elovl6 is a major transcriptional target of sterol regulatory element-binding protein (SREBP) 1, a critical modulator for fatty acid-lipid biosynthesis and glucose metabolism [ 8 , 9 ]. Clinically, genetic variations in the Elovl6 gene have a significant association with insulin sensitivity in population-based studies [ 10 , 11 ]. Elovl6 is expressed ubiquitously and is unique in its role for de novo fatty acid biosynthesis [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, Morcillo et al reported that the risk of insulin resistance was decreased when the rs6824447 mutation was present, while the risk increased in individuals with the rs17041272 mutation (17). On the other hand, Liu et al reported that there were no significant differences regarding those mutations between healthy and type 2 diabetic patients (18). We consider that the association with CD onset is low, because no divergence was found in the frequency of any of the mutations examined in this study.…”
Section: Resultsmentioning
confidence: 47%